Shaped laminate, particularly internal lining part for motor vehicles, as well as process and apparatus for the production thereof - STRICKER; KLAUS; HESS; DIETER W; MAYSENHOELDER; ROLF (1997)
The invention relates to a shaped laminate, particularly an internal lining part for motor vehicles. The laminate (1) has a substantially stiff supporting sheet (2) of thermoplastic material. The latter is covered on at least one and preferably both sides with a surface layer (3, 4) in the form of a nonwoven fabric. The joint between the nonwoven fabric and the plastic sheet is a thermal bond. For forming the bond the nonwoven fabric at least partly and preferably completely is made from the same type of plastic as the sheet. The invention also relates to a process and an apparatus for producing the laminate. For forming the adhesive joint the sheet is heated on at least one side to a temperature in the adhesive range of the thermoplastic material, the sheet interior being kept at a lower temperature. As a result of this procedure the nonwoven fabric structure is protected during the adhesion and shaping process. The invention makes it possible in simple manner to produce type-pure laminates, so that they can be recycled again as a whole, as can the waste material produced during their production.